Septic coxitis after an intramuscular injection in a young adult treated by two-steps total hip arthroplasty: a case report. (2018) - Piolanti, Nicola; Giuntoli, Michele; Nucci, Anna Maria; Bonicoli, Enrico; Parchi, Paolo Domenico; Scaglione, Michelangelo
Abstract: Introduction: Septic arthritis of the hip is a rare condition in adults and its treatment depends on symptoms duration: early onset of infection can be treated with open or arthroscopic debridement, while more aggressive surgery is required when articular damage takes place such as articular resection or total hip replacement (THA). Presentation of case: We report a case of a 30 year old man affect by septic arthritis of the hip after an intramuscular injection of diclofenac successfully treated with a two-steps THA. Discussion: In literature there aren't many cases of septic arthritis of the hip developed after intramuscular injections. Early onset of infection can be treated with an accurate articular debridement, while chronic conditions are traditionally treated by resection arthroplasty. However resection arhtroplasty gives to the patients a significant leg length discrepancy and, especially in young adults, a two-steps surgery with the implant of THA can lead to good results, as reported in recent case series published. Conclusion: In our experience two-stage total hip arthroplasty proved to be a reliable solution for septic arthritis of the hip and may be used in patient with severe joint damage. Furthermore we want underline importance of correct anamnesis to make quickly the right diagnosis and provide the right treatment of septic arthritis of the hip also in difficult clinical cases. Highlights: Primary septic arthritis of the hip is a rare condition in adult population. Early onset of infection can be treated with an accurate articular debridement. Chronic conditions are traditionally treated by resection arthroplasty. Two-stage total hip arthroplasty proved to be a reliable solution for septic arthritis of the hip.